Good Corporate Governance and Corporate Social Responsibility on Company Value - Ellen Rusliati; Rieke Anneesha Ridwan (Management Institute Faculty of Economics Universitas Andalas, 2021)
Company value is an assessment by investors of the company's overall performance which is often associated with stock prices. Maximizing the company value also means maximizing the prosperity of the shareholders. The purpose of this study is to find out the effect of Good Corporate Governance (GCG) Corporate Social Responsibility (CSR) on company value in the coal mining companies listed on the Indonesian Stock Exchange for the period of 2014-2018. Sample of 7 companies are determined by purposive sampling. The type of data used is secondary data using a panel data regression. The results of this study indicated that GCG and CSR have positive significant effect on company value, simultanously and partially. The implementation of GCG and CSR can increase company value, however, GCG has a bigger contribution and effect on it.